(untitled) (Research, Society and Development, 2021)
The objective of this text is to reflect on historical, cultural aspects and anthropic actions in rural areas in the exploration of environmental resources, in the northern region of the state of Rio Grande do Sul. post-colonization and insertion of European migrants in the 20th century, the establishment of relations of production and use of natural resources and impacts generated by agricultural production. Therefore, it uses bibliographical sources, theoretical reflections and a diagnostic study carried out in twelve municipalities in the region. It points to the need to build new cultural perspectives, public policies, training programs and environmental education, in order to develop a collective social awareness capable of expanding the sustainable use of environmental resources, enabling the development of rural properties and the strengthening of chains productive.